Associations of B‐Type Natriuretic Peptide and Its Coding Gene Promoter Methylation With Functional Outcome of Acute Ischemic Stroke: A Mediation Analysis - Aili Wang; Mingzhi Zhang; Yi Ding; Xingbo Mo; Chongke Zhong; Zhengbao Zhu; Daoxia Guo; Xiaowei Zheng; Tan Xu; Yan Liu; Yonghong Zhang; Hao Peng (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background The prognostic role of B‐type natriuretic peptide (BNP) in stroke has been suggested, but limited studies have shown mixed results and unknown underlying mechanisms. DNA methylation, a molecular modification that alters gene expression, may represent a candidate mechanism for this purpose. We aimed to examine the associations of BNP and methylation of its coding gene (natriuretic peptide B [NPPB]) with the functional outcome in a large sample of patients with acute ischemic stroke from CATIS (China Antihypertensive Trial in Acute Ischemic Stroke). Methods and Results Leveraging participants from CATIS with available specimens, serum proBNP (equimolarly produced with BNP) was measured in 3216 patients (mean age, 62 years; 64% men), and peripheral blood DNA methylation of the NPPB promoter was quantified by targeted bisulfite sequencing in 806 patients (mean age, 62 years; 54% men). The functional outcome was defined as an ordered modified Rankin Scale score assessed at 14 days or hospital discharge after stroke onset. Mediation analysis was conducted to test the potential mediating effect of proBNP on the relationship between NPPB methylation and functional outcome. The results showed that a higher level of proBNP was significantly associated with a higher risk of having a poorer functional outcome (odds ratio [OR], 1.14; P=0.006). Every 5% of hypermethylation at 2 (Chr1:11919160 [OR, 0.93; P=0.022] and Chr1:11918989 [OR, 0.92; P=0.032]) of 11 CpG loci assayed was associated with 7% and 8% lower risk, respectively, of having a poor functional outcome. In addition, proBNP was negatively correlated to hypermethylation at 1 CpG (Chr1:11918989 [β=−0.029; P=0.009]) and mediated approximately 7.69% (95% CI, 2.50%–13.82%) of the association between this CpG methylation and the functional outcome. Conclusions Hypermethylation at the NPPB promoter is associated with the functional outcome after ischemic stroke, at least partially by suppressing BNP expression or excretion.